On the reciprocal relationship between job insecurity and employee well-being: Mediation by perceived control? - Vander Elst, Tinne; Van den Broeck, Anja; De Cuyper, Nele; De Witte, Hans (Journal of occupational and organizational psychology, 2014)
This study aims to explain the reciprocal relationship between job insecurity and employee well‐being (i.e., emotional exhaustion and vigour) by perceived control. Building on appraisal theory and conservation of resources theory, we suggest that perceived control mediates the cross‐lagged relationships from job insecurity to employee well‐being, and from employee well‐being to job insecurity. These hypotheses were tested using repeated‐measures data (two waves) from 536 Flemish employees from different organizations and sectors. First, cross‐lagged structural equation modelling analyses showed an effect from job insecurity to perceived control, and from perceived control to emotional exhaustion, so that perceived control (partially) mediated the positive cross‐lagged relationship from job insecurity to emotional exhaustion. Second, we established a cross‐lagged effect from emotional exhaustion to perceived control, although not from perceived control to job insecurity. Third, no cross‐lagged paths were found between perceived control and vigour. This study contributes to both appraisal theory and conservation of resources theory by investigating reciprocal relationships that fit the transactional conceptualization of stress within both frameworks. Furthermore, the results of this study highlight perceived control as the process through which the stressor job insecurity impacts on employee well‐being. Practitioner points The current study suggests a possible theoretical explanation of the negative consequences of job insecurity for employee well‐being: Perceived control accounted for the effect of job insecurity on emotional exhaustion. Job insecurity enhances emotional exhaustion by decreasing employees' feelings of control. Therefore, interventions providing employees with a sense of control, such as communication programmes and measures that promote participative decision‐making, may provide a deterrent to this effect. The current study additionally adds to our knowledge of the impact of employee well‐being on evaluations of the work situation: Emotional exhaustion was found to be related to reduced perceived control over the work situation. Practitioners may want to invest in measures that stimulate employee well‐being, for example job design. This may increase employees' perceptions of control, which then makes them less vulnerable to stressors. Additionally, by fostering both employee well‐being and perceived control, practitioners may forestall a loss cycle between poor well‐being and lack of control.